On the Ionosphere–Atmosphere–Lithosphere Coupling During the 9 November 2022 Italian Earthquake - Mirko Piersanti; Giulia D’Angelo; Dario Recchiuti; Fabio Lepreti; Paola Cusano; Enza De Lauro; Vincenzo Carbone; Pietro Ubertini; Mariarosaria Falanga (Geosciences)
In the last decades, the scientific community has been focused on searching earthquake signatures in the Earth’s atmosphere, ionosphere, and magnetosphere. This work investigates an offshore Mw 5.5 earthquake that struck off the Marche region’s coast (Italy) on 9 November 2022, with a focus on the potential coupling between the Earth’s lithosphere, atmosphere, and magnetosphere triggered by the seismic event. Analysis of atmospheric temperature data from ERA5 reveals a significant increase in potential energy (Ep) at the earthquake’s epicenter, consistent with the generation of Atmospheric Gravity Waves (AGWs). This finding is further corroborated by the MILC analytical model, which accurately simulates the observed Ep trends (within 5%), supporting the theory of Lithosphere–Atmosphere–Ionosphere–Magnetosphere coupling. The study also examines the vertical Total Electron Content (vTEC) and finds notable fluctuations at the epicenter, exhibiting periodicities (7–12 min) characteristic of AGWs and traveling ionospheric disturbances. The correlation between ERA5 observations and MILC model predictions, particularly in temperature deviations and Ep distributions, strengthens the hypothesis that earthquake-generated AGWs impact atmospheric conditions at high altitudes, leading to observable ionospheric perturbations. This research contributes to a deeper understanding of Lithosphere–Atmosphere–Ionosphere–Magnetosphere coupling mechanisms and the potential for developing reliable earthquake prediction tools.